Glueing grids and clouds together: a service-oriented approach. (24th September 2012) - Anjum, Ashiq; Hill, Richard; McClatchey, Richard; Bessis, Nik; Branson, Andrew
Scientific communities are actively developing services to exploit the capabilities of service-oriented distributed systems. This exploitation requires services to be specified and developed for a range of activities such as management and scheduling of workflows and provenance capture and management. Most of these services are designed and developed for a particular community of scientific users. The constraints imposed by architectures, interfaces or platforms can restrict or even prohibit the free interchange of services between disparate scientific communities. Using the notion of 'Platform as a Service' (PaaS), we propose an architectural approach that addresses these limitations so that users can make use of a wider range of services without being concerned about the development of cross-platform middleware, wrappers or any need for bespoke applications. The proposed architecture shields the details of heterogeneous Grid/Cloud infrastructure within a brokering environment, thus enabling users to concentrate on the specification of higher level services.